Defining the functional response of Mycobacterium sp. infected macrophages to structural variants of Interferon gamma (IFN-y) - Nyangwa, Soyama Sivatho (Stellenbosch : Stellenbosch University, 2026)
Thesis (PhD)--Stellenbosch University, 2026.